2016
DOI: 10.1002/jmrs.175
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric and radiobiological impact of intensity modulated proton therapy and RapidArc planning for high‐risk prostate cancer with seminal vesicles

Abstract: IntroductionThe purpose of this study was to evaluate the dosimetric and radiobiological impact of intensity modulated proton therapy (IMPT) and RapidArc planning for high‐risk prostate cancer with seminal vesicles.MethodsTen high‐risk prostate cancer cases were included in this retrospective study. For each case, IMPT plans were generated using multiple field optimisation (MFO) technique (two fields) with XiO treatment planning system (TPS), whereas RapidArc plans were generated using double‐arc technique (tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…The PTV volume is enlarged by prostate hypertrophy and T3b disease, thus affecting the rectal dose. PBT is known to deliver a lower dose to the rectum and bladder, particularly in high-risk cases where seminal vesicle irradiation is required ( 32 , 33 ), which supports the results of the present study.…”
Section: Discussionsupporting
confidence: 91%
“…The PTV volume is enlarged by prostate hypertrophy and T3b disease, thus affecting the rectal dose. PBT is known to deliver a lower dose to the rectum and bladder, particularly in high-risk cases where seminal vesicle irradiation is required ( 32 , 33 ), which supports the results of the present study.…”
Section: Discussionsupporting
confidence: 91%
“…[ 31 32 ] Many studies have suggested that radiobiological modeling that can instantly represent local tumor control and normal tissue complications is a key factor in choosing the optimal radiotherapy technique. [ 33 34 35 ]…”
Section: Discussionmentioning
confidence: 99%
“…The 𝑎 value is typically chosen to be negative value for the tumour. In the case of prostate cancer, the value 𝑎 = −10 is used [16,10]. From the general point The TCP can be calculated based on the EUD value [11,12]:…”
Section: Methodsmentioning
confidence: 99%